2015
DOI: 10.1039/c5ta03442f
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin stabilized magnetic Fe3S4 nanoparticles for efficient removal of Pb(ii)

Abstract: In this study, the magnetic β-cyclodextrins stabilized Fe3S4 nanoparticles (CD-Fe3S4) were fabricated via a facile one-step route. The as-prepared CD-Fe3S4 exhibited a high Pb (II) adsorption capacity of 256 mg g -1 , and it also showed a surprisingly efficient adsorption toward Zn (II), Cd (II), and Cu (II). XRD, FTIR and XPS analyses suggested that the mechanisms governing Pb (II) removal by CD-Fe3S4 were precipitation (formation of galena) and surface adsorption. Additionally, the magnetic property of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…It is usually an authigenic ferromagnetic mineral that forms as a metastable precursor of pyrite in anoxic sedimentary environments during early diagenetic sedimentary sulfate reduction [33,34]. Due to its ferromagnetic and reductive properties, Fe 3 S 4 has been widely used as material for ion batteries designing, carbon dioxide reduction and pollutants remediation [35][36][37][38]. Our previous study demonstrated that the structural sulfide of Fe 3 S 4 enhanced the organoarsenic adsorption and reduction, and its reductive and adsorptive capabilities were extremely dependent on the solution pH [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually an authigenic ferromagnetic mineral that forms as a metastable precursor of pyrite in anoxic sedimentary environments during early diagenetic sedimentary sulfate reduction [33,34]. Due to its ferromagnetic and reductive properties, Fe 3 S 4 has been widely used as material for ion batteries designing, carbon dioxide reduction and pollutants remediation [35][36][37][38]. Our previous study demonstrated that the structural sulfide of Fe 3 S 4 enhanced the organoarsenic adsorption and reduction, and its reductive and adsorptive capabilities were extremely dependent on the solution pH [39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the adsorbent is expected to showcase high porosity, large surface area, and strong binding-site accessibility for adsorbates to result in rapid removal and high adsorption capacity. [24][25][26][27][28][29][30] As an example, the recent study by Zhenghui Li et al has proved the advantage of porous structures for excellent adsorption of organic pollutants in water. 31 The recent past has seen extensive research on the interaction of toxic pollutants with monolayer-protected metal nanoclusters (MNCs) for the advanced development of better sensing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…d shows the appearance of only one Pb doublet, with Pb 4f 7/2 at 138.5 eV and Pb 4f 5/2 at 143.4 eV binding energies, respectively. This doublet may be associated to the presence of Pb–O bonding . In summary, it can be concluded that the surface species, Ag 2 S, Sb 2 O 5 , and PbO were formed at the surface of gold particles, for gold cyanidation carried out with stibnite and Ag minerals.…”
Section: Resultsmentioning
confidence: 83%